Step-by-step explanation:
2x = y-10
Rewrite as: 2x + 10 = y
Therefore:
2x+10 = y
2x +7 = 2y
Subtract the equations:
2x + 10 = y
- 2x + 7 = 2y
______________
3 = -y
Therefore y = -3
Substiture y = -3 into the second equation:
2x + 7 = 2(-3)
2x + 7 = -6
2x = -13
x= -6.5
Answer : (-6.5, -3)
2016^2016 = 2^10080 * 3^ 4032 * 7^2016
so the answer is 1
Answer is option C 19.64 sq units
3 tens= 30
7 tenths= 0.7
8 hundredths= 0.08
so 30+ 0.7+0.08= 30.78
Maybe I’m wrong but I tried... I added 4y to both sides and added -10 + 4y and got -6y and I bring down the -X and divided it by both sides and divided it to the -6y and my answer is -6y